A shot of zinc a day... - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Using traditional plant breeding techniques, researchers at the International Rice Research Institute (IRRI) have developed a rice variety which is naturally rich in iron and zinc, two vital micronutrients that are normally deficient in a rice-heavy...